Managing, Marketing, and Maintaining Maritime and Coastal Tourism. - Brito, M.; Dias, Á.; Patuleia, M. (2020)
The extraordinary beauty, cultural wealth, and diversity of EU's coastal areas have designated them as one of the preferred destinations for many holiday-goers. The numerous businesses that operate in these heavily traveled areas have to struggle with other similarly-minded companies and with providing sustainable practices for the people and surrounding area. Managing, Marketing, and Maintaining Maritime and Coastal Tourism is a pivotal reference source that provides vital material on the application of multidisciplinary and interdisciplinarity logic surrounding sea tourism. While highlighting topics such as destination marketing, event management, and global business, this publication explores the dynamic capabilities and the methods of overall management of hospitality by the sea. This book is ideally designed for marketers, advertisers, tour directors, cruise directors, travel agents, port managers, coastal cities managers, event coordinators, academics, students, researchers, policymakers, public managers, and tourism entrepreneurs.